1998
DOI: 10.1021/ja973109o
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular Nonbonded S···O Interaction Recognized in (Acylimino)thiadiazoline Derivatives as Angiotensin II Receptor Antagonists and Related Compounds

Abstract: The intramolecular nonbonded 1,5-type S···O interactions are recognized in the crystalline structures of the (acylimino)thiadiazoline derivatives (1−3) as angiotensin II receptor antagonists. The relative stability of the nonbonded 1,5-type S···O interaction was investigated using the X-ray crystallographic analyses and the ab initio MO calculations (HF/3-21G*, 6-31G*, and 6-311+G**) of the simplified model compounds (6, 7, and 9). The concept of mimic-fused bicyclic heterocycles consisting of fairly stable no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
188
0
2

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 260 publications
(195 citation statements)
references
References 20 publications
(17 reference statements)
2
188
0
2
Order By: Relevance
“…In this model, 13a can form hydrogen bonds with the kinase back bone via the urea and carbamoyl moieties. Furthermore, it is likely that the urea group of the tricyclic furan is constrained to lie in-plane with the benzothienofuran ring by two intramolecular interactions: i) a hydrogen bond between the urea proton and the amide carbonyl and ii) a non-bonded S· · · O interaction 22) between the oxygen atom of urea carbonyl and the sulfur atom on the thiophene ring. The later is particularly important to increase IKKb inhibition, which is confirmed by the reduced potency observed when the intramolecular non-bonded S· · · O interaction is lost by conversion of the thiophene to other rings (13a vs. 21, 26a, b, and 32).…”
Section: Resultsmentioning
confidence: 99%
“…In this model, 13a can form hydrogen bonds with the kinase back bone via the urea and carbamoyl moieties. Furthermore, it is likely that the urea group of the tricyclic furan is constrained to lie in-plane with the benzothienofuran ring by two intramolecular interactions: i) a hydrogen bond between the urea proton and the amide carbonyl and ii) a non-bonded S· · · O interaction 22) between the oxygen atom of urea carbonyl and the sulfur atom on the thiophene ring. The later is particularly important to increase IKKb inhibition, which is confirmed by the reduced potency observed when the intramolecular non-bonded S· · · O interaction is lost by conversion of the thiophene to other rings (13a vs. 21, 26a, b, and 32).…”
Section: Resultsmentioning
confidence: 99%
“…interactions have been observed in a large number of organosulfur compounds controlling the conformation of small and large molecules. [1][2][3][4][5][6][7][8][9][10][11][12] Some of these compounds showed the strong bioactivity, and we suggested that the intramolecular nonbonded S · · · X interactions play an important role on the mechanism of several biological effects.1,2,6-12) For example, the clear S · · · O close contact in the complex crystalline structure of carbonic anhydrase I and acetazolamide was recognized.12) The same nonbonded interaction was observed in the crystalline structure of acyliminothiadiazoline, which has potent angiotensin II receptor antagonistic activity. 6,11) It is estimated that the ring structure consisted of the intramolecular nonbonded S · · · X interactions was more flexible than that of covalent bonding, and this flexibility increased the binding affinity of the active compound to the flexible pocket of the enzyme or the receptor.…”
mentioning
confidence: 99%
“…interactions have been observed in a large number of organosulfur compounds controlling the conformation of small and large molecules. [1][2][3][4][5][6][7][8][9][10][11][12] Some of these compounds showed the strong bioactivity, and we suggested that the intramolecular nonbonded S · · · X interactions play an important role on the mechanism of several biological effects. 1,2,[6][7][8][9][10][11][12] For example, the clear S · · · O close contact in the complex crystalline structure of carbonic anhydrase I and acetazolamide was recognized.…”
mentioning
confidence: 99%
“…In a similar manner, with arylcopper reagents (e.g., Ar 2 Cu · MgBr · MgBrI), the salt MgBrI should coordinate with the sulfinyl oxygen in monodentate form. Alternatively, transition state B, which would arise due to such an intramolecular nonbonded S-O interaction, 15) is also possible; however, the observed diastereoselectivities were not consistent. When the de values obtained for (di)alkylcopper reagents were compared to those observed for (di)arylcopper reagents, a sterically bulky substituent has no significant influence on the asymmetric induction.…”
Section: )mentioning
confidence: 88%